Rekomendasi untuk Situs Web DMO (Destination Management Organization) Wonderful Indonesia Berdasarkan Dimensi Informasi pada Model ICTRT - I Putu Sudhyana Mecha (Jurnal Pariwisata Terapan, 2019)
Website is one kind of information media that can be used as intermediaries of tourism information. Related to that matter, Wonderful Indonesia tourism website has an important role as national-level DMO (Destination Management Organization). However, it has not been recognized yet as something important in term of tourism, especially when viewed from information dimension. Therefore, evaluation based on IPA (Importance-Performance Analysis) was carried out in order to arrange recommendation for Wonderful Indonesia tourism website. Sampling was conducted to travel agencies from ASITA (Association of Indonesian Tours & Travel Agencies) Bali, as the representative of tourism practitioners. Moreover, considering their role as intermediaries between tourism information and the tourists. Based on the results of evaluation, there was two indicators, such as accommodation information and local weather information that needed to be paid more attention. Regarding the evaluation above, further interviews were also conducted in order to get cross-check feedback, so it can be more convincing as recommendation. The interview was based on the experts that coming from government, practitioner, and academics related to tourism as stakeholders, so the recommendation for Wonderful Indonesia website is expected to be proper use according to the needs of users of tourism information.